Pernikahan Online Dalam Perspektif Fiqh Nawazil - Taufiq, Muhammad; Badruddin Amin, Mohammad; Salem Ahmed, Ahmed; Umar Hafiz Mohammad Idrees, Mohammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Online marriage is a phenomenon of the global Muslim community, which raises different opinions from Islamic jurists about its validity because there is no Al Qur’an argument and hadith text, so it requires legal elaboration. This article discusses the online marriage practice as a phenomenon of contemporary Muslim society and online marriage from the perspective of fiqh nawazil. Thus, the arguments (nash) of the online marriage phenomenon can be explained clearly and comprehensively. This research used normative method with a conceptual, philosophical, and comparative approach between maslahat and mafsadat. The study results show that online marriage is a marriage carried out using online media, such as video calls, Zoom meetings, Webex, and Skype. Online marriage has fulfilled the pillars of marriage, but some conditions that have not been fulfilled, i.e., ijab and qabul, must be said in one location. The use of fiqh nawazil is very suitable to be used as a theory of analysis by using one rule, namely